An attenuated Shigella mutant lacking the RNA-binding protein Hfq provides cross-protection against Shigella strains of broad serotype. - Jiro Mitobe; Ritam Sinha; Soma Mitra; Dhrubajyoti Nag; Noriko Saito; Ken Shimuta; Nobuo Koizumi; Hemanta Koley (Public Library of Science (PLoS), 2017)
Few live attenuated vaccines protect against multiple serotypes of bacterial pathogen because host serotype-specific immune responses are limited to the serotype present in the vaccine strain. Here, immunization with a mutant of Shigella flexneri 2a protected guinea pigs against subsequent infection by S. dysenteriae type 1 and S. sonnei strains. This deletion mutant lacked the RNA-binding protein Hfq leading to increased expression of the type III secretion system via loss of regulation, resulting in attenuation of cell viability through repression of stress response sigma factors. Such increased antigen production and simultaneous attenuation were expected to elicit protective immunity against Shigella strains of heterologous serotypes. Thus, the vaccine potential of this mutant was tested in two guinea pig models of shigellosis. Animals vaccinated in the left eye showed fewer symptoms upon subsequent challenge via the right eye, and even survived subsequent intestinal challenge. In addition, oral vaccination effectively induced production of immunoglobulins without severe side effects, again protecting all animals against subsequent intestinal challenge with S. dysenteriae type 1 or S. sonnei strains. Antibodies against common virulence proteins and the O-antigen of S. flexneri 2a were detected by immunofluorescence microscopy. Reaction of antibodies with various strains, including enteroinvasive Escherichia coli, suggested that common virulence proteins induced protective immunity against a range of serotypes. Therefore, vaccination is expected to cover not only the most prevalent serotypes of S. sonnei and S. flexneri 2a, but also various Shigella strains, including S. dysenteriae type 1, which produces Shiga toxin.